Efficacy and safety of available treatments for visceral leishmaniasis in Brazil: A multicenter, randomized, open label trial. - Gustavo Adolfo Sierra Romero; Dorcas Lamounier Costa; Carlos Henrique Nery Costa; Roque Pacheco de Almeida; Enaldo Viera de Melo; Sílvio Fernando Guimarães de Carvalho; Ana Rabello; Andréa Lucchesi de Carvalho; Anastácio de Queiroz Sousa; Robério Dias Leite; Simone Soares Lima; Thais Alves Amaral; et al. (Public Library of Science (PLoS), 2017)
There is insufficient evidence to support visceral leishmaniasis (VL) treatment recommendations in Brazil and an urgent need to improve current treatments. Drug combinations may be an option.A multicenter, randomized, open label, controlled trial was conducted in five sites in Brazil to evaluate efficacy and safety of (i) amphotericin B deoxycholate (AmphoB) (1 mg/kg/day for 14 days), (ii) liposomal amphotericin B (LAMB) (3 mg/kg/day for 7 days) and (iii) a combination of LAMB (10 mg/kg single dose) plus meglumine antimoniate (MA) (20 mg Sb+5/kg/day for 10 days), compared to (iv) standard treatment with MA (20 mg Sb+5/kg/day for 20 days). Patients, aged 6 months to 50 years, with confirmed VL and without HIV infection were enrolled in the study. Primary efficacy endpoint was clinical cure at 6 months. A planned efficacy and safety interim analysis led to trial interruption.378 patients were randomized to the four treatment arms: MA (n = 112), AmphoB (n = 45), LAMB (n = 109), or LAMB plus MA (n = 112). A high toxicity of AmphoB prompted an unplanned interim safety analysis and this treatment arm was dropped. Per intention-to-treat protocol final analyses of the remaining 332 patients show cure rates at 6 months of 77.5% for MA, 87.2% for LAMB, and 83.9% for LAMB plus MA, without statistically significant differences between the experimental arms and comparator (LAMB: 9.7%; CI95% -0.28 to 19.68, p = 0.06; LAMB plus MA: 6.4%; CI95% -3.93 to 16.73; p = 0.222). LAMB monotherapy was safer than MA regarding frequency of treatment-related adverse events (AE) (p = 0.045), proportion of patients presenting at least one severe AE (p = 0.029), and the proportion of AEs resulting in definitive treatment discontinuation (p = 0.003).Due to lower toxicity and acceptable efficacy, LAMB would be a more suitable first line treatment for VL than standard treatment. ClinicalTrials.gov identification number: NCT01310738.ClinicalTrials.gov NCT01310738.